Eccrine chromhidrosis: A case report and review of literature - Xu, Li-Na; Qiao, Jian-Jun; Fang, Hong (Indian Journal of Case Reports, 2018)
Chromhidrosis is a rare disorder characterized by colored sweat and/or stained skin. Eccrine chromhidrosis is an orphan disease in which water-soluble pigments are excreted through the eccrine glands. This article provides a highly doubtful eccrine chromhidrosis case and the literature review for eccrine chromhidrosis. We recommend an investigative algorithm for dermatologists, hepatologist, and general practitioners to enhance diagnostic capability without mistake among similar and differential diseases. Most importantly, the exact etiology should be determined, which further decides the treatment plan. Systemic treatment of liver diseases or bacteremia was reported particularly effective. Results and prognosis were excellent and without recurrence.